AVALIAÇÃO DA EFICIÊNCIA PRODUTIVA DE MATRIZES NA FAZENDA UEMS - TEIXEIRA, Edvan Correia; FERNANDES, Henrique Jorge; DEVECHIO, Gracielle Chaves; MORAES, Luana Prado; SILVA, Gislaine Jara; LARA, Renato Oliveira Dorna (ANAIS DO ENIC, 2025)
-